Evaluation of chemical fluorescent dyes as a protein conjugation partner for live cell imaging. - Yoko Hayashi-Takanaka (Public Library of Science (PLoS), 2014)
To optimize live cell fluorescence imaging, the choice of fluorescent substrate is a critical factor. Although genetically encoded fluorescent proteins have been used widely, chemical fluorescent dyes are still useful when conjugated to proteins or ligands. However, little information is available for the suitability of different fluorescent dyes for live imaging. We here systematically analyzed the property of a number of commercial fluorescent dyes when conjugated with antigen-binding (Fab) fragments directed against specific histone modifications, in particular, phosphorylated H3S28 (H3S28ph) and acetylated H3K9 (H3K9ac). These Fab fragments were conjugated with a fluorescent dye and loaded into living HeLa cells. H3S28ph-specific Fab fragments were expected to be enriched in condensed chromosomes, as H3S28 is phosphorylated during mitosis. However, the degree of Fab fragment enrichment on mitotic chromosomes varied depending on the conjugated dye. In general, green fluorescent dyes showed higher enrichment, compared to red and far-red fluorescent dyes, even when dye:protein conjugation ratios were similar. These differences are partly explained by an altered affinity of Fab fragment after dye-conjugation; some dyes have less effect on the affinity, while others can affect it more. Moreover, red and far-red fluorescent dyes tended to form aggregates in the cytoplasm. Similar results were observed when H3K9ac-specific Fab fragments were used, suggesting that the properties of each dye affect different Fab fragments similarly. According to our analysis, conjugation with green fluorescent dyes, like Alexa Fluor 488 and Dylight 488, has the least effect on Fab affinity and is the best for live cell imaging, although these dyes are less photostable than red fluorescent dyes. When multicolor imaging is required, we recommend the following dye combinations for optimal results: Alexa Fluor 488 (green), Cy3 (red), and Cy5 or CF640 (far-red).